Development and validation of a histological index for UC. Issue 1 (16th October 2015) - Mosli, Mahmoud H; Feagan, Brian G; Zou, Guangyong; Sandborn, William J; D'Haens, Geert; Khanna, Reena; Shackelton, Lisa M; Walker, Christopher W; Nelson, Sigrid; Vandervoort, Margaret K; Frisbie, Valerie; Samaan, Mark A; et al.
Abstract : Objective: Although the Geboes score (GS) and modified Riley score (MRS) are commonly used to evaluate histological disease activity in UC, their operating properties are unknown. Accordingly, we developed an alternative instrument. Design: Four pathologists scored 48 UC colon biopsies using the GS, MRS and a visual analogue scale global rating. Intra-rater and inter-rater reliability for each index and individual index items were measured using intraclass correlation coefficients (ICCs). Items with high reliability were used to develop the Robarts histopathology index (RHI). The responsiveness/validity of the RHI and multiple histological, endoscopic and clinical outcome measures were evaluated by analyses of change scores, standardised effect size (SES) and Guyatt's responsiveness statistic (GRS) using data from a clinical trial of an effective therapy. Results: Inter-rater ICCs (95% CIs) for the total GS and MRS scores were 0.79 (0.63 to 0.87) and 0.80 (0.69 to 0.87). The correlation estimates between change scores in RHI and change score in GS and MRS were 0.75 (0.67 to 0.82) and 0.84 (0.79 to 0.88), respectively. The SES and GRS estimates for GS, MRS and RHI were: 1.87 (1.54 to 2.20) and 1.23 (0.97 to 1.50), 1.29 (1.02 to 1.56) and 0.88 (0.65 to 1.12), and 1.05 (0.79 to 1.30) and 0.88 (0.64 to 1.12), respectively. Conclusions: The RHI is a new histopathological index with favourable operating properties.